INCREASING TEACHERS CREATIVITY THROUGH STRENGTHENING LEARNING SUPERVISION AND ACHIEVEMENT MOTIVATION - Kamaludin Rizal Hariri; Sutji Harijanto; Sumardi Sumardi (UNIVERSITAS PAKUAN, 2022)
This study uses a correlational approach, and SITOREM analysis consists of two independent variables, namely Learning Supervision and Achievement Motivation, and the dependent variable, Teacher Creativity. This research was conducted in Madrasah Ibtidaiyah in Tenjolaya District in April 2022, with a study population of 142, and there were 106 samples selected using proportional random sampling. The method used in this research is survey and data analysis techniques, with statistical tests of correlation and simple linear regression, and multiple linear regression. The results obtained are as follows, namely: first, there is a significant positive relationship between the Learning Supervision variable (X1) and teacher creativity (Y) with the form of the regression equation = 60.831 + 0.405 X1 and the correlation coefficient ry1 = 0.469 and the correlation coefficient r2y1 = 0.220. Second, there is a significant positive relationship between Achievement Motivation (X2) and teacher creativity (Y) with the form of the regression equation = 51.451 + 0.498 X2 and the correlation coefficient ry2 = 0.498 and the coefficient of determination r2y2 = 0.248. Third, there is a positive and significant relationship between the variables of Learning Supervision (X1) and Achievement Motivation (X2) together with teacher creativity (Y) expressed in the form of a regression equation = 20.939 + 0.269 X1 + 0.445 X2 with correlation coefficient ry12 = 0.572 and the coefficient of determination r2y12 = 0.328. Based on these things, it can be concluded that teacher creativity can be improved through strengthening learning supervision and achievement motivation